Arginine Catabolism in the Cyanobacterium Synechocystis sp. Strain PCC 6803 Involves the Urea Cycle and Arginase Pathway - Quintero, María José (American Society for Microbiology, 2000)
Cells of the unicellular cyanobacterium Synechocystis sp. strain PCC 6803 supplemented with micromolar concentrations of l-[(14)C]arginine took up, concentrated, and catabolized this amino acid. Metabolism of l-[(14)C]arginine generated a set of labeled amino acids that included argininosuccinate, citrulline, glutamate, glutamine, ornithine, and proline. Production of [(14)C]ornithine preceded that of [(14)C]citrulline, and the patterns of labeled amino acids were similar in cells incubated with l-[(14)C]ornithine, suggesting that the reaction of arginase, rendering ornithine and urea, is the main initial step in arginine catabolism. Ornithine followed two metabolic pathways: (i) conversion into citrulline, catalyzed by ornithine carbamoyltransferase, and then, with incorporation of aspartate, conversion into argininosuccinate, in a sort of urea cycle, and (ii) a sort of arginase pathway rendering glutamate (and glutamine) via Δ(1)pyrroline-5-carboxylate and proline. Consistently with the proposed metabolic scheme (i) an argF (ornithine carbamoyltransferase) insertional mutant was impaired in the production of [(14)C]citrulline from [(14)C]arginine; (ii) a proC (Δ(1)pyrroline-5-carboxylate reductase) insertional mutant was impaired in the production of [(14)C]proline, [(14)C]glutamate, and [(14)C]glutamine from [(14)C]arginine or [(14)C]ornithine; and (iii) a putA (proline oxidase) insertional mutant did not produce [(14)C]glutamate from l-[(14)C]arginine, l-[(14)C]ornithine, or l-[(14)C]proline. Mutation of two open reading frames (sll0228 and sll1077) putatively encoding proteins homologous to arginase indicated, however, that none of these proteins was responsible for the arginase activity detected in this cyanobacterium, and mutation of argD (N-acetylornithine aminotransferase) suggested that this transaminase is not important in the production of Δ(1)pyrroline-5-carboxylate from ornithine. The metabolic pathways proposed to explain [(14)C]arginine catabolism also provide a rationale for understanding how nitrogen is made available to the cell after mobilization of cyanophycin [multi-l-arginyl-poly(l-aspartic acid)], a reserve material unique to cyanobacteria.